Water-based aluminum ash fire extinguishing agent and preparation method thereof
By preparing a water-based aluminum ash fire extinguishing agent containing aluminum ash, the shortcomings of existing water-based fire extinguishing agents in terms of fire extinguishing efficiency and environmental protection are solved, efficient and environmentally friendly fire extinguishing effects are achieved, and environmental pollution is reduced.
Patent Information
- Application Number
- CN202411499083.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-25
AI Technical Summary
Existing water-based fire extinguishing agents have shortcomings in fire extinguishing efficiency and environmental protection, especially in terms of efficient fire extinguishing and reducing environmental pollution.
An aqueous aluminum ash fire extinguishing agent is used, and its composition includes distilled water, ammonium dihydrogen phosphate, sodium bicarbonate, urea, disodium EDTA, polyethylene glycol, ethylene glycol, water glass, white carbon black and sodium hydroxide, and aluminum ash as main components, and is prepared by a specific proportioning and stirring process.
The water-based aluminum ash fire extinguishing agent significantly shortens the fire extinguishing time, improves the fire extinguishing efficiency, reduces the possibility of fire spreading, and has low toxicity and low environmental pollution characteristics, which is more environmentally friendly, and waste reuse is achieved by utilizing waste ash.
Smart Images

Figure CN119499600A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fire extinguishing agents, in particular to a water-based aluminum ash fire extinguishing agent and a preparation method thereof. Background Art
[0002] The substances that can effectively destroy the combustion conditions in the combustion zone and suppress or stop the combustion are called fire extinguishing agents. Fire extinguishing agents can be roughly divided into two categories: physical fire extinguishing agents and chemical fire extinguishing agents. Physical fire extinguishing agents do not participate in the combustion reaction. They isolate the air and combustibles during the fire extinguishing process to achieve the effect of extinguishing the fire. They include water, foam, carbon dioxide, nitrogen, helium and other inert gases. Chemical fire extinguishing agents suppress combustion by suppressing the free radical chain reaction in the flame during the combustion process. There are mainly halogenated fire extinguishing agents, dry powder fire extinguishing agents and many other types. The commonly used types of fire extinguishing agents are: water, water vapor, foam fire extinguishing agent, dry powder fire extinguishing agent, carbon dioxide fire extinguishing agent and halogenated alkane fire extinguishing agent.
[0003] As a mature and reliable fire extinguishing agent, water-based fire extinguishing agent has been widely used in many fire scenes and has proved its excellent fire extinguishing effect. Compared with other chemical fire extinguishing agents, water-based fire extinguishing agents have less impact on the environment and human health. It does not produce toxic and harmful byproducts, and with the improvement of environmental awareness, environmentally friendly fire extinguishing agents will be more popular. The application prospects of water-based fire extinguishing agents are very broad, and effectiveness and environmental protection will become the top priority and most important development direction in the field of water-based fire extinguishing agents. Aluminum ash is a solid waste generated in the process of scrap aluminum smelting. The main components of aluminum ash are SiO2, CaC03, Al5(OH) 13 (CO3)·5H2O, etc. These components have the advantages of high melting point, fine particle size, strong ability to block oxygen supply, high temperature resistance, etc., which can achieve the purpose of isolating the fire source and preventing the spread of fire. And the rational use of waste aluminum ash can reduce the pollution of aluminum ash to the environment. For this reason, we propose a water-based aluminum ash fire extinguishing agent and its preparation method. Summary of the invention
[0004] The object of the present invention is to provide a water-based aluminum ash fire extinguishing agent and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a water-based aluminum ash fire extinguishing agent, the water-based aluminum ash fire extinguishing agent comprising component 1 and component 2; wherein component 1 contains distilled water, ammonium dihydrogen phosphate, sodium bicarbonate, urea, disodium EDTA, polyethylene glycol, ethylene glycol, water glass, white carbon black and sodium hydroxide;
[0006] Component 2 is aluminum ash.
[0007] Preferably, in component 1, relative to 100 parts by weight of distilled water, the diammonium phosphate is 2-3 parts by weight, the sodium bicarbonate is 1-2 parts by weight, the urea is 0.3-1 parts by weight, the disodium EDTA is 0.1-0.2 parts by weight, the polyethylene glycol is 0.3-0.8 parts by weight, the ethylene glycol is 0.5-1.5 parts by weight, the water glass is 0.3-1 parts by weight, the white carbon is 0.2-0.8 parts by weight, and the sodium hydroxide is 0.2-0.8 parts by weight.
[0008] Preferably, the aluminum ash is 1.2-3.6 parts by weight relative to 100 parts by weight of distilled water.
[0009] Preferably, the aluminum ash contains Si, Ca, Al, Fe, K, Cl, Zn, Cu and Ti.
[0010] Preferably, the particle size of the aluminum ash is 0.315-126.7 um.
[0011] A preparation method of a water-based aluminum ash fire extinguishing agent comprises the following steps: adding 2.4 parts by weight of ammonium dihydrogen phosphate, 1.6 parts by weight of sodium bicarbonate, 0.6 parts by weight of urea, 0.12 parts by weight of disodium EDTA, 0.6 parts by weight of polyethylene glycol, 1 mL of ethylene glycol, 0.6 parts by weight of water glass, 0.48 parts by weight of white carbon black, 0.45 parts by weight of sodium hydroxide and 3.6 parts by weight of aluminum ash into a stirring device filled with 100 parts by weight of distilled water, and then stirring with a glass rod for a period of time until the mixture is uniform.
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] 1. The water-based aluminum ash fire extinguishing agent and its preparation method are highly efficient. Adding aluminum ash to the traditional water-based aluminum ash fire extinguishing agent can greatly shorten the fire extinguishing time of the fire extinguishing agent, improve its fire extinguishing efficiency, enable it to extinguish the fire more quickly, reduce the possibility of fire spreading, and protect people's lives and property safety; environmentally friendly. The fire extinguishing agent is mainly water-based aluminum ash fire extinguishing agent with low toxicity and low pollution to the environment. Compared with traditional chemical fire extinguishing agents, it is more environmentally friendly and has less impact on the environment. At the same time, the water-based aluminum ash fire extinguishing agent made of aluminum ash can also greatly reduce the pollution of the aluminum ash itself to the environment, thereby achieving the purpose of waste recycling; economical. The fire extinguishing agent is mainly water-based aluminum ash fire extinguishing agent, which has lower cost than some chemical fire extinguishing agents, and is more economical and affordable to be widely used in fire extinguishing equipment and fire-fighting equipment. At the same time, the water-based aluminum ash fire extinguishing agent made of aluminum ash can save the amount of raw materials, thereby reducing the cost of making the fire extinguishing agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 A schematic diagram of the instruments required for the aluminum ash experiment in the present invention;
[0015] Figure 2 A schematic diagram of the reagents required for the aluminum ash experiment in the present invention;
[0016] Figure 3 It is a schematic diagram of the EDX experimental results in the present invention;
[0017] Figure 4 It is a schematic diagram of the XRD experimental results in the present invention;
[0018] Figure 5 It is a schematic diagram of the particle size experimental results in the present invention;
[0019] Figure 6 Schematic diagram of the contact angle test results in the present invention;
[0020] Figure 7 It is a schematic diagram of the effect of different amounts of aluminum ash on the fire extinguishing time in the present invention. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] See also Figures 1 to 7 In an embodiment of the present invention, a water-based aluminum ash fire extinguishing agent includes component 1 and component 2; wherein component 1 contains distilled water, ammonium dihydrogen phosphate, sodium bicarbonate, urea, disodium EDTA, polyethylene glycol, ethylene glycol, water glass, white carbon black and sodium hydroxide;
[0023] Component 2 is aluminum ash.
[0024] Embodiment 1:
[0025] 1. Experimental instruments and reagents:
[0026] The instruments needed for the experiment are as follows: Figure 1 As shown; the reagents required for the experiment are as follows Figure 2 As shown;
[0027] 2. Characterization of aluminum ash:
[0028] 2.1. EDX test:
[0029] Preheat the machine for 30 minutes, open the software, wait for the software to automatically adjust the collimator and filter of the instrument, put in the aluminum ash sample after it stops automatically, click Initialize, select the correct curve related to the sample after successful initialization, click Start, enter the sample name, and import the data into Excel.
[0030] 2.2, XRD test:
[0031] First, prepare the sample (because the aluminum ash powder is fine enough, otherwise it should be ground with an agate mortar first. Coarse particle size will lead to low diffraction intensity, poor peak shape, and low resolution), wipe the tablet pressing tool clean with alcohol, and dry it under a small lamp.
[0032] Use a medicine spoon to transfer the aluminum ash sample to the tablet pressing tank, and the amount is appropriate. Use a tablet press to press the tablet. Open the measurement control system software, confirm that the test conditions are 30 degrees to 50 degrees, and the scanning speed is 0.05 degrees per minute. After confirmation, conduct the test.
[0033] After the test, when the X-ray is turned off, open the sample chamber and take out the sample.
[0034] 2.3, particle size test:
[0035] Turn on the instrument, then turn on the computer, and wait for the instrument to load power (the indicator light on the lower left of the particle size analyzer turns blue). Open the cover of the instrument.
[0036] Double-click Bettersize2000, click the option at the top of the window, adjust the optical parameters, change the English and Chinese names of the substance to the corresponding or closest ones of the sample, and adjust the specific gravity of the sample. Click Test at the top of the window, and then click Auto Test.
[0037] After waiting for a while, when the message "Concentration is too low, please add sample" appears in the upper right corner of the window, you can add the sample (use a metal spoon to take about half a spoonful and add).
[0038] 2.4. Contact angle test:
[0039] Open the contact angle tester, open the lens cover, and turn on the machine. Open the contact angle measurement software and camera, press the aluminum ash sample into a tablet and place the sample, adjust the height distance, left and right distance, zoom range, distance, and light brightness to reduce test errors.
[0040] Distilled water was sucked into the syringe to drip manually, and pictures were exported before dripping, when the water drop was tangent to the sample, and after titration. When the water drop fell into the sample and spread on it, the exported picture was saved on the desktop, and then the picture was fitted to obtain its angle, chord height, arc length, and radius.
[0041] After completing one set of measurements, clean the needle and test three sets.
[0042] 3. Preparation of aluminum ash fire extinguishing agent:
[0043] A. Add 2.4g of diammonium dihydrogen phosphate, 1.6g of sodium bicarbonate, 0.6g of urea, 0.12g of disodium EDTA, 0.6g of polyethylene glycol, 1mL of ethylene glycol, 0.6g of water glass, 0.48g of white carbon black, and 0.45g of sodium hydroxide to a beaker filled with 100mL of distilled water, and then stir with a glass rod for a while until it is uniform.
[0044] B. Add 2.4g of diammonium dihydrogen phosphate, 1.6g of sodium bicarbonate, 0.6g of urea, 0.12g of disodium EDTA, 0.6g of polyethylene glycol, 1mL of ethylene glycol, 0.6g of water glass, 0.48g of white carbon black, 0.45g of sodium hydroxide, and 1.2g of aluminum ash to a beaker filled with 100mL of distilled water, and then stir with a glass rod for a while until it is uniform.
[0045] C. Add 2.4g of diammonium dihydrogen phosphate, 1.6g of sodium bicarbonate, 0.6g of urea, 0.12g of disodium EDTA, 0.6g of polyethylene glycol, 1mL of ethylene glycol, 0.6g of water glass, 0.48g of white carbon black, 0.45g of sodium hydroxide, and 2.4g of aluminum ash to a beaker filled with 100mL of distilled water, and then stir with a glass rod for a while until it is uniform.
[0046] D. Add 2.4 g of diammonium dihydrogen phosphate, 1.6 g of sodium bicarbonate, 0.6 g of urea, 0.12 g of disodium EDTA, 0.6 g of polyethylene glycol, 1 mL of ethylene glycol, 0.6 g of water glass, 0.48 g of white carbon black, 0.45 g of sodium hydroxide, and 3.6 g of aluminum ash to a beaker filled with 100 mL of distilled water, and then stir with a glass rod for a while until it is uniform.
[0047] 4. Fire extinguishing effect test:
[0048] Prepare a large stainless steel bowl, put a piece of filter paper (weigh the mass in advance), and then apply 1mL of alcohol on the filter paper. Add the prepared fire extinguishing agent to the spray bottle, light the filter paper, start timing after two or three seconds, and spray the spray bottle at the fire source at the same time. When the flame is completely extinguished, stop timing. Do four groups separately and compare the fire extinguishing effect. Apply 2mL of alcohol on the filter paper and do four more groups of experiments in the same way to compare the fire extinguishing effect.
[0049] 5. Results and discussion
[0050] 5.1、EDX experimental results are as follows Figure 3 As shown;
[0051] Depend on Figure 3It can be seen that the aluminum ash sample mainly contains Si, Ca, Al, and Fe elements, among which Si has the highest atomic percentage, reaching 28.174%, Ca has the second highest atomic percentage, reaching 25.615%, Al has an atomic percentage of 20.166%, Fe has an atomic percentage of 13.637%, and Ba has the lowest atomic percentage of 0.836%. In addition, the atomic percentages of K, Cl, Zn, Cu, and Ti are also relatively low. The test results are basically consistent with the information provided by the manufacturer.
[0052] 5.2. XRD test results:
[0053] The XRD experimental results are shown in Figure 4 As shown;
[0054] exist Figure 4 The first one is the peak diagram, which shows that the peak shape is relatively narrow. The amorphous sample is a large package peak without a fine spectrum peak structure, which confirms that the sample is not amorphous but crystalline. The second one is a curve fitting of the peak diagram, which has a total of 52 peaks. The third one is the phase diagram, which shows that the aluminum ash sample is mainly composed of SiO2, CaCO3, Al5(OH) 13 (CO3)·5H2O、Ca2Al4Si4O 15 The phases of (OH)2, Ca(Al, Si)2O4, and Ca4Al2O6Cl2·10H2O are compared with the standard spectrum. The peaks near 26.5° and 21° are the main characteristic peaks of SiO2, the peak near 29.3° is the main characteristic peak of CaCO3, and the diffraction peaks near the diffraction angle 2θ of 38° and 50° are Al5(OH) 13 The main characteristic peak of (CO3)·5H2O is the diffraction peak of Ca2Al4Si4O near 2θ 40.5°. 15 The main characteristic peaks of (OH)2, the peaks near the diffraction angles 2θ of 31° and 68.1° may be the diffraction peaks of Ca(Al, Si)2O4, and the peak near the diffraction angle 2θ of 42.5° may be the diffraction peak of Ca4Al2O6Cl2·10H2O.
[0055] 5.3. Particle size test results:
[0056] The particle size test results are as follows Figure 5 As shown;
[0057] Depend on Figure 5It can be obtained that D10 is 1.737um, that is, 10% of the particles have a diameter less than 1.737um, the median diameter D50 is 13um, that is, half of the particles are larger than 13um, and half of the particles are smaller than 13um, and D90 is 46.74um, that is, 90% of the particles have a diameter less than 46.74um. Generally speaking, D50 is the most meaningful for reference. From the particle size distribution curve, it is found that the sample particle size range is 0.315um-126.7um, and the vertical lines of the three data of D10, D50, and D90 are relatively close, indicating that the particle distribution is narrow and the concentration is high. The closer the particle size is to the average value, the better the uniformity of the particles. It can be seen from Table 2 that the uniformity of the particles is good.
[0058] 5.4. Contact angle test results:
[0059] The contact angle test results are as follows: Figure 6 As shown:
[0060] This test uses the sessile drop method. As can be seen from the picture, the shape of the water drop is ellipsoidal. During the test, when the water drop contacts and is tangent to the aluminum ash sample, it is found that the water drop first maintains an ellipsoidal shape and is easily stained with the sample. The height of the needle tube is raised, and the water drop spreads on the aluminum ash sample after falling. The angle of the first group is 26.1716 degrees, the angle of the second group is 25.4628 degrees, and the angle of the third group is 26.9903 degrees. The average angle of the three groups is 26.2749 degrees, as shown in the table. It can be clearly seen from the table that the chord height, arc length, and radius of the first group are slightly different from those of the other two groups. This may be because there is a certain error in the measurement. The average angle is less than 90 degrees, which indicates that the aluminum ash surface is hydrophilic. The angle between each group does not differ by more than one degree, indicating that the error of the overall test is relatively small.
[0061] 5.5. Fire extinguishing effect test results:
[0062] The effect of different amounts of aluminum ash on fire extinguishing time is as follows Figure 7 As shown;
[0063] Depend on Figure 7It can be seen that water is the blank group, group A is the control group without aluminum ash, group B adds 1.2g aluminum ash on the basis of group A, group C adds 2.4g aluminum ash on the basis of group A, and group D adds 3.6g aluminum ash on the basis of group A. When the amount of ethanol added and the mass of filter paper are equal, the extinguishing time of the four groups of fire extinguishing agents, ABCD, is much less than that of water, and the extinguishing time is from least to most in the order of DCBA. When 1mL of ethanol is added, the extinguishing time of the fire extinguishing agent without aluminum ash is 7.37s, the extinguishing time of the fire extinguishing agent with 1.2g aluminum ash is 6.89s, which is 0.48s lower, the extinguishing time of the fire extinguishing agent with 2.4g aluminum ash is 6.63s, which is 0.26s lower than the second group, and the extinguishing time of the fire extinguishing agent with 3.6g aluminum ash is 4. 57s, which is 2.06s lower than the third group; when 2mL of ethanol is added, the extinguishing time of water is 21.11s, the extinguishing time of the fire extinguishing agent without adding aluminum ash is 8.14s, the extinguishing time of the fire extinguishing agent with 1.2g of aluminum ash is 8.02s, which is 0.12s lower, the extinguishing time of the fire extinguishing agent with 2.4g of aluminum ash is 7.51s, which is 0.51s lower than the second group, and the extinguishing time of the fire extinguishing agent with 3.6g of aluminum ash is 5.89s, which is 1.62s lower than the third group. This shows that within a certain range, the more aluminum ash is added, the shorter the extinguishing time, that is, the better the fire extinguishing effect, and the aluminum ash added cannot be too much, otherwise it will change the fire extinguishing composition. This result may be because the aluminum ash covers it and isolates the air. For the same group, for example, when the amount of ethanol added in group A increased from 1 mL to 2 mL, the fire extinguishing time changed from 7.37 s to 8.14 s, indicating that the more ethanol was added, the longer the fire extinguishing time was, i.e., the worse the fire extinguishing effect was.
[0064] 5.6. Study on the performance of water-based aluminum ash fire extinguishing agent prepared from aluminum ash:
[0065] In the EDX test, Figure 1 It can be seen that the main elements contained in aluminum ash are silicon, calcium, aluminum, and iron. In the XRD test, Figure 3 It can be seen that the aluminum ash sample is mainly composed of SiO2, CaCO3, Al5(OH) 13 (CO3)·5H2O、Ca2Al4Si4O 15 (OH)2, Ca(Al, Si)2O4, Ca4Al2O6Cl2·10H2O. Aluminum ash is mainly composed of calcium, aluminum, and silicon compounds. In the particle size test, Figure 5 It can be seen that the particle size of aluminum ash is very small, with a median diameter of 13 microns. The aluminum ash powder is very fine, which provides favorable conditions for contact with water. In the contact angle test, Figure 6 It can be seen that water droplets spread easily on the sample surface and aluminum ash has a certain hydrophilicity. In summary, aluminum ash can be used to prepare water-based aluminum ash fire extinguishing agent.
[0066] 6. Conclusion:
[0067] Through EDX test, XRD test, particle size test and contact angle test, it can be known that aluminum ash mainly contains Si, Ca, Al, Fe elements, and contains a small amount of K, Cl, Zn, Cu, Ti, Ba elements. The aluminum ash sample is mainly composed of SiO2, CaCO3, Al5(OH) 13 (CO3)·5H2O、Ca2Al4Si4O 15 (OH)2, Ca(Al, Si)2O4, Ca4Al2O6Cl2·10H2O, these phase compositions show that the aluminum ash sample is mainly composed of compounds containing calcium, aluminum, and silicon, and the test results are basically consistent with the information provided by the manufacturer. In the particle size test, it can be seen that the aluminum ash sample has good particle uniformity, and at the same time, water drops are easy to spread on the aluminum ash sample after falling. Aluminum ash is hydrophilic, which shows that it is feasible to prepare water-based aluminum ash fire extinguishing agent from aluminum ash. Through the fire extinguishing test, it was found that the fire extinguishing effect of the fire extinguishing agent with aluminum ash added is better than that of the original fire extinguishing agent without aluminum ash, and within a certain range, the more aluminum ash content, the better the fire extinguishing effect. By utilizing and turning aluminum ash, a solid waste, not only its harm to the environment is reduced, but also the amount of raw materials used is saved.
[0068] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A water-based aluminum ash fire extinguishing agent, characterized in that: The water-based aluminum ash fire extinguishing agent includes component 1 and component 2; wherein component 1 contains distilled water, ammonium dihydrogen phosphate, sodium bicarbonate, urea, disodium EDTA, polyethylene glycol, ethylene glycol, water glass, white carbon black and sodium hydroxide; Component 2 is aluminum ash.
2. The aqueous aluminum ash fire extinguishing agent according to claim 1, characterized in that: In component 1, relative to 100 parts by weight of distilled water, the diammonium phosphate is 2-3 parts by weight, the sodium bicarbonate is 1-2 parts by weight, the urea is 0.3-1 parts by weight, the disodium EDTA is 0.1-0.2 parts by weight, the polyethylene glycol is 0.3-0.8 parts by weight, the ethylene glycol is 0.5-1.5 parts by weight, the water glass is 0.3-1 parts by weight, the white carbon is 0.2-0.8 parts by weight, and the sodium hydroxide is 0.2-0.8 parts by weight.
3. The water-based aluminum ash fire extinguishing agent according to claim 1, characterized in that: Relative to 100 parts by weight of distilled water, the aluminum ash is 1.2-3.6 parts by weight.
4. The water-based aluminum ash fire extinguishing agent according to claim 1, characterized in that: The aluminum ash contains Si, Ca, Al, Fe, K, Cl, Zn, Cu and Ti.
5. The water-based aluminum ash fire extinguishing agent according to claim 1, characterized in that: The particle size of the aluminum ash is 0.315-126.7 um.
6. The method for preparing a water-based aluminum ash fire extinguishing agent according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: adding 2.4 parts by weight of ammonium dihydrogen phosphate, 1.6 parts by weight of sodium bicarbonate, 0.6 parts by weight of urea, 0.12 parts by weight of disodium EDTA, 0.6 parts by weight of polyethylene glycol, 1 mL of ethylene glycol, 0.6 parts by weight of water glass, 0.48 parts by weight of white carbon black, 0.45 parts by weight of sodium hydroxide and 3.6 parts by weight of aluminum ash into a stirring device filled with 100 parts by weight of distilled water, and then stirring with a glass rod for a period of time until the mixture is uniform.